RISK FACTORS AND TREATMENT FOR TINNITUS AMONG ADOLESCENTS - Tomanic, Milena; Belojevic, Goran; Cvorovic, Ljiljana; Mladenovic, Dusan; Ilic Zivojinovic, Jelena; Davidovic, Dragana; Jovanovic, Ana; Djurdjevic, Katarina (Medical Research, 2023)
SummaryIntroduction: Tinnitus is the conscious perception of sound without an external sound stimulus. The origin of the name is in the root of the Latin word tinnire (to ring). The sound can be buzzing, ringing, hissing, and rarely as a voice, music, or several different sounds simultaneously. Tinnitus occurs in one-third of people at least once in their lifetime and is chronic in 10-15% of the adult population. In children and adolescents aged 5 to 19 years, the range of tinnitus prevalence is quite wide (from 5% to over 40%), depending on how tinnitus is defined in the study. This article aims to provide an up-to-date overview of tinnitus risk factors and treatment in adolescents.Methods: The authors searched PubMed, Embase, and Cochrane Review databases using the keywords: tinnitus, adolescents, risk behaviors, risk factors, and treatment. The inclusion criterion was that the article was published in Serbian or English without time restriction. Results: Common risk factors for tinnitus among adolescents are female gender, noise exposure, hearing loss, marijuana and tobacco smoking and exposure to second-hand smoke, and sleep deprivation. Recently, some nutritional risk factors have been added: lack of water intake, niacin and protein deficits, and consumption of sweetened sodas, fast food, and white bread. The results of the current treatment of tinnitus, either pharmaceutical, surgical, or behavioral, are unsatisfactory, causing frustration among patients and physicians. Currently, there is no registered medicine for tinnitus.Conclusion: Tinnitus is one of the greatest enigmas of modern medicine. As tinnitus is still considered incurable, we point out major risk factors among adolescents that should be targeted in primary prevention.  Key Words: tinnitus, adolescents, risk behaviors, risk factors, and treatment.